We’ve Come a Long Way, Baby: Announcing a Special Issue to Commemorate the Publication of Molecule’s 20,000th Paper - Farid Chemat; Roman Dembinski; Arnaud Gautier; James W. Gauld; Derek McPhee; Diego Muñoz-Torrero; Joselito P. Quirino; Thomas J. Schmidt; Vadim A. Soloshonok; Mark von Itzstein (Molecules, 2019)
On behalf of my Section Editor-in-Chief co-author colleagues I am pleased to announce a Special Issue to commemorate the recent publication of Molecules’ 20,000th paper [...]